Method for improving mechanical property of powder core wire electric arc additive titanium-based composite material

Through the two-step post-treatment process of thermal isostatic pressing and heat treatment, the pore defect problem in the titanium-based powder core wire printing components is solved, significantly improving the mechanical properties of the material, and meeting the demand for high-end equipment for high-performance materials.

CN119794377APending Publication Date: 2025-04-11HARBIN INST OF TECH

Patent Information

Application Number
CN202510003436.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The titanium-based powder core wire printing components have pore defects, resulting in poor plastic toughness and fatigue performance, which cannot meet the demand for high-performance materials of high-end equipment.

Method used

A two-step post-treatment process is adopted: firstly eliminate the pores by thermal isostatic pressure, and then heat treatment is carried out to refine the structure, forming a bistate structure of isometric + sheet layer, and improving the mechanical properties of the material.

Benefits of technology

By eliminating air pores and refining the structure, the mechanical properties of titanium-based composite materials are significantly improved, and the problems of long process, high cost and high machine-added problems are solved, meeting the demand for high-end equipment for high-performance materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794377A_ABST
    Figure CN119794377A_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the mechanical property of a powder core wire electric arc additive titanium-based composite material. The invention relates to a method for improving the mechanical property of a powder core wire electric arc additive titanium-based composite material. The invention aims to solve the problems that a component printed by the existing titanium-based powder core wire has air hole defects and is poor in plasticity, toughness and fatigue performance. The method comprises the following steps: 1, adding the titanium-based composite material to the powder core wire material through electric arc; 2, cleaning a printed piece; 3, hot isostatic pressing; and 4, heat treatment. The method is used for improving the mechanical property of the powder core wire electric arc additive titanium-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the mechanical properties of a powder core wire arc additive titanium-based composite material. Background Art

[0002] In the field of high-end technology such as modern aerospace and national defense, the continuous evolution of advanced equipment has continuously raised expectations for material performance. As a representative national heavy weapon, the harsh working environment of hypersonic aircraft requires materials to have excellent comprehensive performance. Titanium-based composite materials, with titanium alloy as the matrix, cleverly introduce reinforcing phases such as TiB, TiC, Ti5Si3 (in situ or externally), with high specific strength, relatively low density and good heat resistance, have emerged among many high-performance materials. Compared with traditional titanium alloys, it can increase the service temperature by about 200°C. This feature makes it possible to significantly reduce the weight of components by as much as 50% in aircraft structural applications if it replaces existing in-service high-temperature alloy materials. In this way, the maneuverability of the aircraft can be greatly improved, and the cruising range can be effectively extended, which is of great significance to improving the overall combat effectiveness and mission adaptability of the aircraft.

[0003] However, despite the huge advantages of titanium-based composite materials in theoretical performance, they face many thorny problems in the actual manufacturing process of aircraft components. The traditional manufacturing process commonly used at this stage covers multiple complex links such as casting, powder metallurgy, thermal deformation and machining. This multi-step process chain is not only lengthy and cumbersome, but also leads to high manufacturing costs. More importantly, since the titanium-based composite components used in aircraft are often produced in small batches and have large structures, the difficulty of machining increases sharply when dealing with the manufacturing of such components by traditional processes, which undoubtedly brings huge obstacles to the efficient and high-quality production of such components. Therefore, there is an urgent need to explore and develop a new, more adaptable and economical manufacturing process to meet the growing demand for high-performance titanium-based composite components in the aerospace and defense fields.

[0004] As an important branch in the field of metal 3D printing, arc fuse additive manufacturing technology has shown unique technical advantages. Compared with traditional laser beam and electron beam additive manufacturing technologies, the energy contained in the arc is higher, which significantly accelerates the fuse rate and can deposit more materials per unit time, thereby effectively improving manufacturing efficiency. At the same time, compared with the powder feeding additive manufacturing process, the wire feeding process has the significant advantage of less raw material splashing, which not only reduces the waste of raw materials and improves material utilization, but also makes the molten pool more stable, which is conducive to precise control of the forming process, thereby achieving a near-net forming effect. This near-net forming capability means that in the manufacturing process, only a small amount of subsequent processing is required to obtain components that meet the precision requirements, greatly reducing the workload and difficulty of mechanical processing. Therefore, arc fuse additive manufacturing technology has unique advantages in the rapid manufacture of large-size titanium-based composite components in small batches, and it also has great potential in reducing the manufacturing cost of components, becoming an attractive technical direction to solve the current difficulties in the manufacturing of titanium-based composite components.

[0005] However, when arc fuse additive manufacturing technology is applied to the manufacture of titanium-based composite materials, it encounters a key bottleneck problem - the limitation of raw materials. Specifically, the wire required by this technology is an essential raw material, and there is currently a lack of composite wires specifically for titanium-based composite materials. The existing wires are mainly titanium alloy wires, which are only suitable for the manufacture of titanium alloys and cannot meet the requirements for the introduction of reinforcing phases in titanium-based composite materials, resulting in the development of arc fuse additive manufacturing technology for titanium-based composite materials almost stagnating.

[0006] In recent years, the emergence of titanium-based powder core wires has brought new hope for breaking this bottleneck. Titanium-based powder core wires are an innovative type of flux-cored wires with a unique structural design. They use pure titanium as the outer skin and are filled with specific reinforcement powders (such as TiB2, B4C, C powder, etc.) and alloy powders (such as Al, V, Zr, Mo powder, etc.) inside. During the arc fuse deposition process, the outer skin of the wire enters the molten pool together with the internal powder. As the molten pool solidifies, the reinforcement phase can precipitate in situ, thus successfully forming a titanium-based composite material. However, although titanium-based powder core wires theoretically provide the possibility for arc fuse additive manufacturing of titanium-based composite materials, in practical applications, components printed with this type of wire have serious porosity defects. This is due to inherent factors such as impurities in the powder core gap, inert gas entrapment, and composite material molten pool characteristics. It is difficult to solve this problem simply by optimizing printing parameters, which directly leads to a significant reduction in the plastic toughness and fatigue performance of the components, and cannot meet the strict requirements of high-performance components for high-end equipment such as aircraft.

[0007] Hot isostatic pressing sintering technology has a wide range of application history and rich practical experience in the field of metal material preparation. Its basic principle is to achieve the densification process of the powder by applying a pressure of up to hundreds of MPa to the gas in a sealed container. The metal ingot obtained after hot isostatic pressing can reach a nearly dense state. In addition to being used to prepare metal materials, hot isostatic pressing technology is also widely used in the thermal densification treatment of cast workpieces. It can effectively eliminate defects such as shrinkage and shrinkage cavities generated inside the workpiece during the casting process, and significantly improve the quality and performance of the workpiece. In the field of powder metallurgy of titanium alloys and titanium-based composites, hot isostatic pressing technology has also been applied to a certain extent and has achieved some beneficial results.

[0008] However, when hot isostatic pressing technology is applied to the densification of arc-added titanium-based composites, it is found that the relevant process parameters used in titanium alloy and titanium-based composite powder metallurgy cannot be directly copied. This is mainly due to the differences in the following key factors: First, in the hot isostatic pressing powder metallurgy process, the powder is carefully filled in a vacuum-treated package. This special treatment method enables the powder to form a huge pressure difference between the inside and outside during the hot isostatic pressing process. This pressure difference plays an extremely favorable role in promoting the powder densification process. In arc-added titanium-based composites, the inside of the pores is not a vacuum environment, but is filled with various gases and impurities, which greatly increases the difficulty of closing the pores during the hot isostatic pressing process, which is essentially different from the traditional powder metallurgy process. Second, the choice of hot isostatic pressing temperature has a crucial influence on the densification effect and final performance of titanium-based composites. If the hot isostatic pressing temperature is too high, although it may be beneficial to the closure of pores, it will also cause the reinforcement to coarsen, which will weaken the strengthening effect of the reinforcement in the composite material and reduce the performance of the material; on the contrary, if the hot isostatic pressing temperature is too low, it will not provide enough energy and driving force for the pore closure, which is not conducive to the effective closure of the pores and the densification of the material cannot be achieved. Third, after hot isostatic pressing, the matrix structure often shows serious coarsening, which will directly lead to a significant decrease in the mechanical properties of the material. Therefore, in order to compensate for the adverse effects of hot isostatic pressing on the matrix structure, it is necessary to carefully design a reasonable heat treatment process, through a specific heating, insulation and cooling process, to achieve the refinement of the matrix structure, so as to restore and improve the mechanical properties of the material.

[0009] In summary, in the context of the increasingly urgent demand for high-performance titanium-based composite components in the aerospace and defense fields, the limitations of traditional manufacturing processes, the raw material bottleneck and pore defect problems of arc fuse additive manufacturing technology, and the inadaptability of process parameters when hot isostatic pressing technology is applied to the densification treatment of arc additive titanium-based composites are intertwined. There is an urgent need to develop a comprehensive method that can effectively improve the mechanical properties of powder-cored wire arc additive titanium-based composites, so as to break through the difficulties of existing technologies and provide solid material technology support for the development of advanced equipment such as hypersonic aircraft. Summary of the invention

[0010] The present invention aims to solve the problems of pore defects, poor plasticity, toughness and fatigue performance of components printed by existing titanium-based powder core wires, and to provide a method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials.

[0011] A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to the present invention is carried out in the following steps:

[0012] 1. Printing: Using titanium flux-cored welding wire as raw material, arc fuse technology is used to print titanium-based composite workpieces;

[0013] 2. Cleaning: Use wire cutting to remove the titanium-based composite material workpiece from the substrate surface, and sequentially wash with water, alkali and acid to remove dust, oil and oxide layer on the workpiece surface to obtain a cleaned workpiece;

[0014] 3. Hot isostatic pressing: Using argon as the pressure medium, the cleaned workpiece is placed in a hot isostatic pressing furnace for thermal densification to obtain a workpiece after thermal densification;

[0015] 4. Heat treatment: placing the workpiece after heat densification treatment in a muffle furnace for heat treatment to obtain a powder core wire arc additive titanium-based composite material.

[0016] Beneficial effects of the present invention:

[0017] The present invention uses a two-step post-processing process to eliminate pores while maintaining a refined structure, greatly improving the mechanical properties of components. The purpose of the present invention is to optimize the powder core wire arc additive manufacturing technology, realize arc additive manufacturing of high-performance titanium-based composite components, and solve the problems of long traditional preparation processes, high costs, and difficult machining.

[0018] Hot isostatic pressing is combined with heat treatment. During hot isostatic pressing, the pore closing deformation will locally recrystallize to form equiaxed α grains; and through subsequent heat treatment, the non-porous area is transformed into a fine lamellar structure, obtaining an equiaxed + lamellar dual-state structure, and the mechanical properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A physical picture of the TiB / TA15 composite thin wall printed in the embodiment;

[0020] Figure 2 This is a comparison chart of the porosity of TiB / TA15 composite materials in the printed state, hot isostatic pressing state, and hot isostatic pressing + heat treatment state;

[0021] Figure 3 The microstructures of TiB / TA15 composite materials in the printed state, hot isostatic pressing state, and hot isostatic pressing + heat treatment state; a represents the printed state, b represents the hot isostatic pressing state, and c represents the hot isostatic pressing + heat treatment state. DETAILED DESCRIPTION

[0022] Specific implementation method 1: A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials in this implementation method is carried out in the following steps:

[0023] 1. Printing: Using titanium flux-cored welding wire as raw material, arc fuse technology is used to print titanium-based composite workpieces;

[0024] 2. Cleaning: Use wire cutting to remove the titanium-based composite material workpiece from the substrate surface, and sequentially wash with water, alkali and acid to remove dust, oil and oxide layer on the workpiece surface to obtain a cleaned workpiece;

[0025] 3. Hot isostatic pressing: Using argon as the pressure medium, the cleaned workpiece is placed in a hot isostatic pressing furnace for thermal densification to obtain a workpiece after thermal densification;

[0026] 4. Heat treatment: placing the workpiece after heat densification treatment in a muffle furnace for heat treatment to obtain a powder core wire arc additive titanium-based composite material.

[0027] This embodiment can ensure that the pressure and temperature act evenly on the inside of the material during the hot isostatic pressing process by thoroughly cleaning the surface, avoiding problems such as uneven densification caused by surface impurities, and is also conducive to uniform transformation of the structure during heat treatment.

[0028] This embodiment can effectively promote pore closure, reduce the internal porosity of the material, and improve the density of the material while taking into account unfavorable factors such as the non-vacuum environment inside the pores. The appropriate temperature will not cause excessive coarsening of the reinforcement, but can provide sufficient energy for pore closure. The combination of pressure and holding time can also ensure the densification effect, thereby improving the strength and other mechanical properties of the material.

[0029] This embodiment performs hot isostatic pressing under specific parameters. High temperature makes atoms active and enhances the diffusion capacity of atoms, which is extremely critical for closing pores. On the one hand, it helps to eliminate pores formed by air and water vapor impurities entering the molten pool in the powder core gap and pores caused by inert gas being drawn into the molten pool. On the other hand, at this temperature, considering the presence of high melting point ceramic phases in titanium-based composite materials, it can provide suitable energy conditions for pore closure without causing excessive coarsening of the reinforcement, balancing the needs of reinforcement stability and pore elimination. The application of pressure causes the pores and pores inside the material to be uniformly squeezed in all directions, and cooperates with high temperature to promote the deformation and closure process of the pores. The holding time ensures that this process can be fully carried out, so that the density of the material is significantly improved, and the stress concentration points caused by the presence of pores are reduced, laying the foundation for the subsequent improvement of the comprehensive performance of the material. At the same time, using argon as the pressure medium effectively prevents adverse chemical reactions such as oxidation of the material under high temperature and high pressure environments, ensuring the chemical stability and performance reliability of the material.

[0030] In this embodiment, the heat treatment includes solid solution and aging; the combination of solid solution temperature and time allows the alloy elements in the titanium-based composite material to fully dissolve into the matrix to form a uniform solid solution state. Water cooling or air cooling can effectively inhibit the precipitation of alloy elements during the cooling process, so that the material obtains an oversaturated solid solution structure, thereby producing a significant solid solution strengthening effect and greatly improving the strength index of the material. Moreover, the solid solution treatment process can adjust and optimize the microstructural inhomogeneity that may exist after hot isostatic pressing to a certain extent, refine the grain size, improve the grain boundary structure, further reduce stress concentration, and improve the toughness reserve of the material. On the basis of the supersaturated solid solution, the aging treatment promotes the precipitation of alloy elements in the form of fine dispersed strengthening phases and uniformly distributes them in the matrix, producing a strong dispersion strengthening effect and continuously improving the strength of the material. At the same time, the aging process accurately controls the precipitation morphology of the strengthening phase (precipitated is silicide (Ti, Zr) 5Si3), size and distribution, optimizes the grain boundary characteristics, reduces micro defects, and effectively improves the plastic toughness and fatigue properties of the material. Appropriate aging treatment can make the grain boundaries smoother, reduce the probability of crack initiation, and improve the material's fatigue resistance under cyclic loading conditions; and by controlling the precipitation amount and distribution uniformity of the strengthening phase, the material's plastic deformation ability is enhanced while maintaining high strength, thereby fully overcoming the problem of poor plastic toughness and fatigue performance of the material after simple hot isostatic pressing treatment.

[0031] In this embodiment, hot isostatic pressing first solves the density problem of the material and provides a relatively uniform and dense matrix structure for subsequent heat treatment; if there is no hot isostatic pressing to reduce pores and increase density in advance, the presence of defects such as pores during the heat treatment process will lead to uneven organizational transformation, more complex stress distribution, and the strengthening effect cannot be effectively achieved. Heat treatment further optimizes the microstructure and performance of the material on the basis of hot isostatic pressing. Solution treatment adjusts and strengthens the organization after hot isostatic pressing, and aging treatment further refines and optimizes the organization. The combination of the two not only improves the strength of the material, but more importantly, improves the plasticity, toughness and fatigue properties. This synergistic effect fundamentally solves the problem of pore defects in titanium-based powder core wire printed components and the resulting poor plasticity, toughness and fatigue performance, so that the comprehensive mechanical properties of the material are comprehensively improved, meeting the strict requirements of high-performance titanium-based composite components in high-end fields such as aerospace.

[0032] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the titanium flux-cored welding wire in step 1 contains ceramic powder, and the ceramic powder content is 0.1-5%. Other steps and parameters are the same as those in specific implementation method 1.

[0033] Specific embodiment 3: This embodiment is different from specific embodiment 2 in that the ceramic powder is one or a combination of several of TiB2, ZrB2, B4C, C and B. Other steps and parameters are the same as those of specific embodiment 2.

[0034] Specific embodiment 4: This embodiment differs from specific embodiment 1 in that: in step 1, arc fuse technology is used to print titanium-based composite material workpieces, and argon gas is blown to prevent the workpiece from oxidizing at high temperature. Other steps and parameters are the same as those in specific embodiment 1.

[0035] Specific embodiment 5: This embodiment differs from specific embodiment 4 in that: the printing parameters in step 1 are: substrate preheating temperature 150°C, printing current 100-250A, printing speed 3-8mm / s, wire feeding speed 0.5-5.0m / min, wire feeding angle 10-30°, and the distance between the tungsten electrode and the workpiece is 5mm. The other steps and parameters are the same as those in specific embodiment 4.

[0036] Specific embodiment 6: This embodiment is different from the specific embodiment 1 in that: the alkaline washing in step 2 is washing with a 2% NaOH aqueous solution for 3 to 5 minutes; the acid washing is washing with an acid solution for 10 to 15 minutes; the acid solution is a mixture of HNO3, HF and H2O in a volume ratio of 1:1:3. The other steps and parameters are the same as those in the specific embodiment 1.

[0037] Specific embodiment 7: This embodiment differs from specific embodiment 1 in that the thermal densification treatment parameters in step 3 are: temperature 800-1000°C, pressure 100-180MPa, holding time 3-6h, and furnace cooling. Other steps and parameters are the same as those in specific embodiment 1.

[0038] Specific embodiment 8: This embodiment differs from specific embodiment 1 in that the heat treatment in step 4 includes solution treatment and aging. The other steps and parameters are the same as those in specific embodiment 1.

[0039] Specific embodiment 9: This embodiment differs from specific embodiment 8 in that the solid solution parameters are: temperature 1000-1100°C, holding time is the thinnest dimension of the workpiece multiplied by 0.8-1.2 min / mm, water cooling or air cooling to room temperature. Other steps and parameters are the same as those of specific embodiment 8.

[0040] Specific embodiment 10: This embodiment differs from specific embodiment 8 in that the aging parameters are: temperature 500-650°C, heat preservation time 0.1-2h, air cooling to room temperature. Other steps and parameters are the same as those of specific embodiment 8.

[0041] The following examples are used to verify the beneficial effects of the present invention:

[0042] Embodiment 1: A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials is carried out in the following steps:

[0043] 1. Printing: Using titanium flux-cored wire (powder core components: 0.4wt% TiB2, 0.12wt% ZrB2, 0.12wt% Si, 6.46wt% Al, 0.99wt.% V, 1.99wt% Zr, 0.99wt% Mo, 21.43wt% Ti) as raw material, TiB / TA15 composite material thin wall printed by arc single-pass reciprocating deposition; printing parameters are: current 170A, printing speed 5mm / s, wire feeding speed 1.0m / min;

[0044] 2. Cleaning: The titanium-based composite material workpiece is removed from the substrate surface by wire cutting, and the workpiece surface dust, oil stains and oxide layer are removed by tap water washing, alkali washing (2 vol.% NaOH aqueous solution, 3 min), and acid washing (HNO3:HF:H2O=1:1:3 (volume ratio), 10 min) to obtain a cleaned workpiece;

[0045] 3. Hot isostatic pressing: Using argon as the pressure medium, the cleaned workpiece is placed in a hot isostatic pressing furnace for thermal densification to obtain a workpiece after thermal densification. The hot isostatic pressing parameters are: temperature 960°C, pressure 150MPa, and holding time 4h.

[0046] 4. Heat treatment: Place the workpiece after heat densification treatment in a muffle furnace for heat treatment to obtain a powder core wire arc additive titanium-based composite material; the heat treatment includes solid solution and aging; the solid solution parameters are: temperature 1050°C, solid solution time 15min, water cooling or air cooling to room temperature; the aging parameters are: temperature 600°C, holding time 1.5h, air cooling to room temperature.

[0047] Figure 1 This is a physical picture of the TiB / TA15 composite material thin wall printed in the embodiment; it can be seen from the figure that the thin wall has good formability, regular shape, and dimensions of about 160mm×10mm×60mm; there are no cracks or other defects in the upper, middle and lower areas of the thin wall and the connection between the thin wall and the base plate, indicating that the use of powder core filaments to print titanium-based composite materials is feasible.

[0048] Figure 2 This is a comparison of the porosity of TiB / TA15 composite materials in the printed state, hot isostatic pressing state, and hot isostatic pressing + heat treatment state. For the printed material, its porosity is 0.74%; after hot isostatic pressing, the porosity drops to 0.008%; after heat treatment, the porosity is 0.08%, which is 10 times lower than that of the printed material. Therefore, hot isostatic pressing can significantly improve the density of the material.

[0049] The pores inside the printed material are formed by bubbles trapped in the molten pool. Assuming that the gas pressure inside the bubble is atmospheric pressure (P0 = 100kPa) and the temperature is 3000K, according to the ideal gas equation PV = nRT, when the molten pool solidifies and cools to room temperature (293K), the pressure inside the pore drops to P1≈10kPa, showing a negative pressure state. During the hot isostatic pressing process, there is a pressure difference (△P = P2-P1 = 100MPa-10kPa≈100MPa) between the gas pressure inside the pore (P1) and the external hot pressing gas pressure (P2 = 100MPa), and at the same time, the yield strength of the TiB / TA15 composite material in the range of 800-1000℃ is only 10-50MPa, which is lower than the gas pressure difference △P. The material around the pore will undergo plastic rheology under the action of the pressure difference, and the pore volume will decrease. Since P2 / P1=10000, theoretically after hot isostatic pressing, the pore volume is reduced by 10000 times (i.e., the porosity is reduced by 10000 times), and the pore diameter is reduced by about 22 times, so the material density is significantly increased.

[0050] Figure 3 The microstructures of TiB / TA15 composite materials in the printed state, hot isostatic pressing state, and hot isostatic pressing + heat treatment state are shown in Figure 1. First, the microstructure of the printed composite material is composed of α / β thin layers with a layer width of 1 μm. Figure 3 (a). After hot isostatic pressing, the width of the sheet increases significantly, and the size is 10 μm. Figure 3(b) This is because the slow cooling during the hot isostatic pressing process leads to the coarsening of the α / β lamellae; due to the selection of a lower hot isostatic pressing temperature, the TiB whiskers did not coarsen, and the large aspect ratio is conducive to the whiskers to play a load transfer strengthening role. After solution heat treatment, the α / β lamellae are significantly refined, and the width is reduced to 0.5-1μm, which is close to the size of the printed fine lamellae. During the 1000℃ solution heat treatment, Ti undergoes an α→β transformation, and the coarse α / β lamellae structure is transformed into a single β phase; in the subsequent air cooling process, β is transformed into α / β lamellae again, and the faster cooling rate inhibits the growth of the α phase, and the α / β lamellae are refined.

[0051] The room temperature tensile properties of the printed and hot isostatically pressed + heat treated TiB / TA15 composites were compared. The strength of the printed composite material is 1020MPa, and the elongation at break is 1.6%, which shows a typical brittle fracture, mainly due to the presence of pore defects inside the printed material. The strength of the hot isostatically pressed composite material is 1000MPa, and the elongation is 4.2%. The decrease in strength is caused by the coarsening of the structure. The strength of the hot isostatically pressed + heat treated composite material is 1044MPa, which is comparable to the printed material, but the elongation at break increases to 6.5%, which is 4 times that of the printed composite material, achieving an effective improvement in plasticity without sacrificing strength, mainly due to a significant decrease in porosity.

[0052] The above examples prove that the two-step post-processing process can significantly improve the mechanical properties of printed titanium-based composites.

Claims

1. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials, characterized in that The method for improving the mechanical properties of powder core wire arc additive titanium-based composites is carried out in the following steps:

1. Printing: Using titanium flux-cored welding wire as raw material, arc fuse technology is used to print titanium-based composite workpieces; 2. Cleaning: Use wire cutting to remove the titanium-based composite material workpiece from the substrate surface, and sequentially wash with water, alkali and acid to remove dust, oil and oxide layer on the workpiece surface to obtain a cleaned workpiece; 3. Hot isostatic pressing: Using argon as the pressure medium, the cleaned workpiece is placed in a hot isostatic pressing furnace for thermal densification to obtain a workpiece after thermal densification; 4. Heat treatment: placing the workpiece after heat densification treatment in a muffle furnace for heat treatment to obtain a powder core wire arc additive titanium-based composite material.

2. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 1, characterized in that The titanium flux-cored welding wire in step 1 contains ceramic powder, and the content of the ceramic powder is 0.1-5%.

3. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 2, characterized in that The ceramic powder is one of TiB2, ZrB2, B4C, C and B or a combination of several thereof.

4. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 1, characterized in that In step 1, arc fuse technology is used to print titanium-based composite workpieces, and argon gas is blown to prevent the workpiece from oxidizing at a high temperature.

5. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 4, characterized in that The printing parameters in step 1 are: substrate preheating temperature 150°C, printing current 100-250A, printing speed 3-8mm / s, wire feeding speed 0.5-5.0m / min, wire feeding angle 10-30°, and the distance between tungsten electrode and workpiece 5mm.

6. The method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 1, characterized in that The alkaline washing in step 2 is performed by using a 2% by volume NaOH aqueous solution for 3 to 5 minutes; the acid washing is performed by using an acid solution for 10 to 15 minutes; the acid solution is a mixture of HNO3, HF and H2O in a volume ratio of 1:1:

3.

7. The method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 1, characterized in that The thermal densification treatment parameters in step three are: temperature 800-1000°C, pressure 100-180MPa, holding time 3-6h, and cooling in the furnace.

8. The method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 1, characterized in that The heat treatment in step 4 includes solution treatment and aging.

9. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 8, characterized in that The solution parameters are: temperature 1000-1100°C, holding time is the thinnest size of the workpiece multiplied by 0.8-1.2 min / mm, water cooling or air cooling to room temperature.

10. A method for improving the mechanical properties of powder core wire arc additive titanium-based composite materials according to claim 8, characterized in that The aging parameters are: temperature 500-650°C, holding time 0.1-2h, and air cooling to room temperature.

Citation Information

Patent Citations

  • Preparation method for titanium flux-cored wire for 3D printing of titanium-based composite material

    CN108000004A

  • Post-treatment method for additive-manufacturing titanium and titanium alloy part

    CN109175376A

  • Method for improving tensile property anisotropy of electric-arc additive manufactured titanium alloy components

    CN110216352A

  • Low-cost titanium alloy wire material for electric arc additive material and manufacturing method of structural part of low-cost titanium alloy wire material

    CN114351004A

  • TC4 titanium alloy welding wire for electric arc additive manufacturing and additive manufacturing method of TC4 titanium alloy welding wire

    CN117102732A

Cited By

  • High-strength titanium alloy powder core wire material special for additive manufacturing and preparation method of component of high-strength titanium alloy powder core wire material

    CN121669957A